Retention of Sodium Alginate-Based Mucoadhesive Ranitidine - Ifa Nurazizah; Suparmi; Kusuma, Aris Perdana (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
Ranitidine, a histamine H2-antagonist, has an oral bioavailability of 50-60% and an elimination half-life of approximately 2 to 3 hours. To enhance its therapeutic efficacy, ranitidine must remain in the stomach for an extended period. A mucoadhesive gastroretentive drug delivery system can improve its bioavailability. This study formulated ranitidine granules using sodium alginate as a polymer via wet granulation. Formulations with varying sodium alginate concentrations (7-11%) were prepared and evaluated for flow properties, tapping properties, moisture content, swelling capacity, and dissolution. The formulation with 11% sodium alginate demonstrated optimal properties. It achieved a flow rate of 12.3±0.23 g/s, an angle of repose of 27.13±0.63°, a compressibility index of 21.35±2.23%, a Hausner ratio of 1.32±0.07, a moisture content of 2.59±0.2%, a swelling index of 72.85±3.48%, and a wash-off time of 77.34±48.75 minutes. Additionally, over 80% of the drug was dissolved. In conclusion, the 11% sodium alginate formulation is the most promising for mucoadhesive ranitidine delivery.